Perencanaan Kebutuhan Pompa Untuk Sistem Dewatering Tambang Emas Desa Bakan Kabupaten Bolaang Mongondow - Putri Hamdan, Annisya; Anshariah, Anshariah; Bakri, Hasbi; Nullah Yusuf, Firman (CV Insight Publisher, 2023)
One of the most frequent problems in open pit mining methods is the presence of water puddles in the lowest elevation of the pit. This often causesthe delay of production activities.Therefore, it is a need to design a good drainage system planning to deal with it. In this regard, pumps were needed. The aim of this research was to determine the of needed pumps and the best type of pumps to remove water in the pit effectively. This research used maps of mining sequence planningwhich would be then analysed with software Surpac 6.5.1.This was to identifythe width of catchment area. Furthermore, the rainfall data wasanalysed using polygon Thiessen method. The next process is to determine the rainfall plan with Gumbel method. Next was to determine the rainfall intensity plan by using Mononobe equations. Following this was determine the total discharge using rational method. Finally, the process was ended with the determining of the pumps type and pumps spesification to dry the water puddles in the pit. the result indicated that in the sump of the 3rd quarter 2020 with 100 l / sec pumping flow, pumping time 14 hours, total head 76.26 m, recommended pump type is a Multiflo MFC 385 with a rotation speed of recommendation per minute of 1400-1500, and an efficiency of 60% -65%. For 4th quarter sump 2020 with 105l / sec pumping discharge, 20 hour pumping time, total head 105,91 m, recommended type of pump is Multiflo MFC 385 with rotation speed recommendation permenit 1600-1700, with efficiency 60%. For the 1st quarter sump 2021 with a pumping rate of 102 l/sec, the pumping time is 20 hours, total head is 122.26 m, the recommended type of pump is Multiflo MFC 385 with a rotation speed of recommendation per minute 1700-1800, with 50% -60% efficiency. It can be suggested that it is necessary to add one more pump, Multiflo MFC 385, for the dewatering pit process.